Evolution and phylogeography of Culex pipiens densovirus - Altinli, M; Lequime, S; Courcelle, M; François, S; Justy, F; Gosselin-Grenet, A-S; Ogliastro, M; Weill, M; Sicard, M (Oxford University Press, 2019)
Viruses of the Parvoviridae family infect a wide range of animals including vertebrates and invertebrates. So far, our understanding of parvovirus diversity is biased towards medically or economically important viruses mainly infecting vertebrate hosts, while invertebrate infecting parvoviruses-namely densoviruses-have been largely neglected. Here, we investigated the prevalence and the evolution of the only mosquito-infecting ambidensovirus, Culex pipiens densovirus (CpDV), from laboratory mosquito lines and natural populations collected worldwide. CpDV diversity generally grouped in two clades, here named CpDV-1 and -2. The incongruence of the different gene trees for some samples suggested the possibility of recombination events between strains from different clades. We further investigated the role of selection on the evolution of CpDV genome and detected many individual sites under purifying selection both in non-structural and structural genes. However, some sites in structural genes were under diversifying selection, especially during the divergence of CpDV-1 and -2 clades. These substitutions between CpDV-1 and -2 clades were mostly located in the capsid protein encoding region and might cause changes in host specificity or pathogenicity of CpDV strains from the two clades. However, additional functional and experimental studies are necessary to fully understand the protein conformations and the resulting phenotype of these substitutions between clades of CpDV.